Primary pulmonary cryptococcosis - Asadi Gharabaghi, Mehrnaz (BMJ Publishing Group, 2014)
Here, we report a case of primary cryptococcal pneumonia in a 25-year-old woman who presented with several weeks’ history of cough, dyspnoea and night sweating. These symptoms started in the third trimester of her pregnancy. She was being treated for infertility and got pregnant with in vitro fertilisation. On chest imaging, there were bilateral air space consolidation and cavitary lesions. Fungal pulmonary infection was diagnosed after surgical lung biopsy. She received fluconazole 400 mg per day orally for 6 months and recovered completely.